Purple urine bag syndrome: a unique clinical case and management considerations - Fatemeh Mahdi; Amirhossein Larijani (BMC Nephrology, 2024)
Abstract Purple urine bag syndrome (PUBS) is a rare and unusual event. It is related to symptomatic urinary infection and asymptomatic bacteriuria in patients with indwelling bladder catheters. The purple color of the urine is due to metabolic products of biochemical reactions formed by bacterial enzymes in the urine. Gastrointestinal tract flora breaks down the amino acid tryptophan into indole, which is subsequently absorbed into the portal circulation and converted into indoxyl sulfate. Indoxyl sulfate is then excreted into the urine, where it can be broken down into indoxyl if the appropriate alkaline environment and bacterial enzymes are present. The breakdown products, indigo, and indirubin appear blue and red. We reported on an elderly woman who was kept in a nursing home, had multiple comorbidities such as history of cerebrovascular accident (CVA), acute kidney injury (AKI) and she was hospitalized due to decreased consciousness, fever and kidney failure. On the third day of hospitalization, the patient developed PUBS while undergoing urinary catheterization in the hospital. She had no history of previous catheterization and chronic use of antibiotics, she was only using Tolterodine for a long time due to urinary urgency. Due to antibiotic resistance, the drugs were not changed and the purple color disappeared after changing the catheter and urinary bag. This was the first patient in this region to be reported with this manifestation.